Toward an innovative function-oriented assessment methodology (FOAM) for evaluating the functional condition of buildings during the operation and maintenance phase - Veronica Royano; Vicente Gibert; Carles Serrat; Jacek Rapinski (Developments in the Built Environment)
This paper introduces a foundational approach toward defining a Function-Oriented Assessment Methodology (FOAM) for evaluating the functional condition of buildings during the operation and maintenance phase. Although various national classification systems exist, a unified international system for organizing construction elements has not been widely adopted. To bridge this gap, the paper proposes adopting an international standard-based classification system for identifying objects within a function-oriented structure. Traditional inspections often focus on damage, overlooking the functional condition of construction elements. This research addresses these limitations with a comprehensive methodological approach tailored to assess functional condition. It employs a multiple-choice questionnaire adapted from international rating scales to ensure consistency and minimize subjectivity among inspectors. A case study validates the effectiveness of this strategic framework, demonstrating high consistency and accuracy in evaluating functional conditions. Overall, this research lays the groundwork for FOAM, offering a clear path for its broader application in the built environment.